Regulation of RNA splicing in endometrial tissue and its association with endometriosis - Fei Yang; Ting Qi; Allan F. McRae; Peter A.W. Rogers; Grant W. Montgomery; Sally Mortlock (iScience)
Summary: The endometrium, essential for reproduction, undergoes cyclical shedding, remodeling, and regeneration. Using a large endometrial transcriptomic dataset (n = 206), we identified RNA splicing and transcript isoform-level changes across the menstrual cycle and in endometriosis, findings not seen in gene-level analyses. Transcriptomic differences were most pronounced in the mid-secretory (receptive) phase in endometriosis samples. By integrating genotype data, we found evidence of cis-genetic effects on splicing in endometrium, identifying 3,296 splicing quantitative trait loci (sQTLs) with the majority of genes with sQTLs (67.5%) not discovered in the gene level eQTLs analysis, indicating the splicing-specific effects. Integrating the sQTLs with the endometriosis genome-wide association study (GWAS) data, we identified two genes (GREB1 and WASHC3) that were significantly associated with endometriosis risk through genetically regulated splicing events. Overall, this study detected transcript isoform-level and RNA splicing level specific changes, providing insights into the dynamic changes in transcriptomic regulation in endometrium and its association with endometriosis.